Psychoeducation on Workplace Bullying at Pondok Pesantren al-Kholafiyah Lumajang - Anugrah Sulistiyowati; Nikmatus Solikhah (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2023)
Bullying is one of the prevalent social phenomena often perpetrated by individuals in our surroundings. This behavior can range from physical violence to psychological abuse. Bullying can occur in various environments, including the workplace, often referred to as workplace bullying. Victims of bullying can experience various issues, such as becoming more introverted, having reduced social interactions, and experiencing decreased self-confidence. Workplace bullying is a recurring act of hostility, aggression, both verbal and non-verbal violence, carried out with the intent to torment, thwart, provoke, intimidate, causing discomfort to the recipient. This consideration is the basis for providing psychoeducation related to workplace bullying. The psychoeducational program aims to enhance the awareness of Al Kholafiyah students regarding the impact and how to respond when cases of workplace bullying occur. The community service is conducted using the Asset-Based Community Development (ABCD) method. The activity proceeds smoothly by presenting real cases and delivering materials on the impact of workplace bullying. Participants gain an understanding of the dangers and consequences of workplace bullying.